Rheb signaling and tumorigenesis: mTORC1 and new horizons. Issue 8 (17th August 2015) - Armijo, Marisol E.; Campos, Tania; Fuentes‐Villalobos, Francisco; Palma, Mario E.; Pincheira, Roxana; Castro, Ariel F.
Abstract : Rheb is a conserved small GTPase that belongs to the Ras superfamily, and is mainly involved in activation of cell growth through stimulation of mTORC1 activity. Because deregulation of the Rheb/mTORC1 signaling is associated with proliferative disorders and cancer, inhibition of mTORC1 has been therapeutically approached. Although this therapy has proven antitumor activity, its efficacy is not as expected. Here, we will review the main work on the identification of the role of Rheb in cell growth, and on the relevance of Rheb in proliferative disorders, including cancer. We will also review the Rheb functions that could explain tumor resistance to therapies with mTORC1 inhibitors, and will mainly focus our discussion on mTORC1‐independent Rheb functions that could also be implicated in cancer cell survival and tumorigenesis. The current progress on the understanding of the noncanonical Rheb functions prompts future studies to establish their relevance in cancer and in the context of current cancer therapies.